2007
DOI: 10.1051/0004-6361:20066651
|View full text |Cite
|
Sign up to set email alerts
|

The INTEGRAL Galactic bulge monitoring program: the first 1.5 years

Abstract: Aims. The Galactic bulge region is a rich host of variable high-energy point sources. Since 2005, February 17 we are monitoring the source activity in the Galactic bulge region regularly and frequently, i.e., about every three days, with the instruments onboard INTEGRAL. Thanks to the large field of view, the imaging capabilities and the sensitivity at hard X-rays, we are able to present for the first time a detailed homogeneous (hard) X-ray view of a sample of 76 sources in the Galactic bulge region. Methods.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
106
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 97 publications
(175 reference statements)
5
106
0
1
Order By: Relevance
“…However, the observed behavior is far from being satisfactorily interpreted within the current bursting theory due to the presence of unexpected short bursts or even absence thereof, in a regime where long bursts would be expected (Kuulkers et al 2007). The reason of this could be that in the case of high accretion rates accretion is unlikely through a plain disk, and the TL configuration may have an extra effect on the bursting behavior.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, the observed behavior is far from being satisfactorily interpreted within the current bursting theory due to the presence of unexpected short bursts or even absence thereof, in a regime where long bursts would be expected (Kuulkers et al 2007). The reason of this could be that in the case of high accretion rates accretion is unlikely through a plain disk, and the TL configuration may have an extra effect on the bursting behavior.…”
Section: Discussionmentioning
confidence: 83%
“…Indeed a hard tail in the spectra of GX 5−1 had already been detected by previous observations (Asai et al 1994;Paizis et al 2005, P06). The second spectrum (7 < HR < 10) shows a weaker hard tail between 40 and 150 keV; the third one (10 < HR < 12) does not show a hard tail and is soft; the last spectrum is the softest (HR > 12), again with no hard tail (see also Kuulkers et al 2007;Paizis et al 2005, on the variability of GX 5−1). As required by the data, we used the two-component model for all spectra in the fitting process and obtained the following results (see Table 3):…”
Section: Gx 5-1mentioning
confidence: 95%
“…Our average value found for 2003 and 2005 is 2.5 ± 0.4 × 10 −9 erg cm −2 s −1 , and our measured value for 2012 is 1.7 ± 0.1 × 10 −9 erg cm −2 s −1 , while the averaged between 2006 and 2008 value measured by Suzaku is 2.2 × 10 −9 erg cm −2 s −1 . It is noteworthy that recent monitoring by the INTEGRAL/IBIS program in the Galactic Bulge reported that 1E 1740.7−2942 is below the detection sensitivity limit (Kuulkers et al 2013).…”
Section: Discussionmentioning
confidence: 95%
“…Swift J1749.4−2807 was detected again in a high X-ray luminosity state on 2010 April 10, during the INTEGRAL Galactic bulge monitoring program (Pavan et al 2010;Kuulkers et al 2007). Swift and RXTE target of opportunity observations (ToO) were immediately requested, and these monitored the source outburst for about two weeks.…”
Section: Swift J17494−2807mentioning
confidence: 99%